1988
DOI: 10.1002/cne.902680403
|View full text |Cite
|
Sign up to set email alerts
|

The central projection of masticatory afferent fibers to the trigeminal sensory nuclear complex and upper cervical spinal cord

Abstract: Retrograde and anterograde transport of horseradish peroxidase-wheat germ agglutinin (HRP-WGA) conjugate was used to study the organization of primary afferent neurons innervating the masticatory muscles. HRP applied to the nerves of jaw-closing muscles--the deep temporal (DT), masseter (Ma), and medial pterygoid (MP)--labeled cells in the trigeminal ganglion and the mesencephalic trigeminal nucleus (Vmes), whereas HRP applied to nerves of the jaw-opening muscles--anterior digastric (AD) and mylohyoid (My)--la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 92 publications
6
96
0
1
Order By: Relevance
“…The rat's head was placed in a stereotaxic frame, the skin over the dorsal surface of the skull reflected and a trephination made on the left side of the skull to allow a microelectrode to be lowered through the brain and into the trigeminal ganglion. The skin, muscle and dura overlying the brainstem and upper cervical spinal cord were removed to permit placement of a stimulating electrode in contact with the brainstem for antidromic activation of brainstem projecting masticatory muscle afferent fibers that have been shown to project predominantly to the caudal brainstem (Shigenaga et al, 1988;Capra and Wax, 1989;Cairns et al, 2001Cairns et al, , 2002. Physiological parameters were continuously monitored throughout the experiment as described above.…”
Section: Afferent Fiber Recordingmentioning
confidence: 99%
“…The rat's head was placed in a stereotaxic frame, the skin over the dorsal surface of the skull reflected and a trephination made on the left side of the skull to allow a microelectrode to be lowered through the brain and into the trigeminal ganglion. The skin, muscle and dura overlying the brainstem and upper cervical spinal cord were removed to permit placement of a stimulating electrode in contact with the brainstem for antidromic activation of brainstem projecting masticatory muscle afferent fibers that have been shown to project predominantly to the caudal brainstem (Shigenaga et al, 1988;Capra and Wax, 1989;Cairns et al, 2001Cairns et al, , 2002. Physiological parameters were continuously monitored throughout the experiment as described above.…”
Section: Afferent Fiber Recordingmentioning
confidence: 99%
“…Studies in rat and cat indicate the TMJ region is innervated mainly by small-diameter myelinated and unmyelinated fibers (Ioi et al 2006;Kido et al 1995;Takeuchi and Toda 2003;Takeuchi et al 2001) that project to second-order neurons at the trigeminal subnucleus caudalis/upper cervical cord (Vc/C1-2) junction (Shigenaga et al 1986(Shigenaga et al , 1988. Lesion of the Vc/C1-2 junction, but not more rostral trigeminal brain stem areas, prevents increases in masseter muscle activity after TMJ inflammation (Hu et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroanatomical studies have shown that the PTN receives input from the periphery through cranial nerves V (Nishimori et al, 1986;Shigenaga et al, 1986Shigenaga et al, , 1988Pfaller and Arvidsson, 1988;Panneton, 1991), IX, and X Mizuno, 1982, 1983;Arvidsson and Thomander, 1984;Hamilton and Norgren, 1984;Altschuler et al, 1989;Nazruddin et al, 1989). Afferent projections coursing in branches of the facial nerve, which have their cell bodies in the nodose ganglion, also terminate in the PTN (Arvidsson and Thomander, 1984).…”
mentioning
confidence: 96%